Contemporary light weight composite material -milestone towards automotive brake rotor application - Maleque, Md. Abdul (2014)
Lightweight materials are significantly replacing heavy materials in the automotive industry in order to compensate weight reduction which in turn translates to energy saving. Efforts by researchers to overcome this limitation give rise to contemporary light weight composite materials which has the potential tribo-mechanical properties to replace automotive tribo-components. Metal matrix composite has the potential weight reduction of approximately 40-55% when compared to cast iron heavy materials. This advantage offers a great flexibility to automotive manufacturers as substitute materials particularly for dynamic loaded components such as brake rotors due to its unsprung mass. In this key note paper, reinforced silicon carbide (SiCp)-aluminium light weight composite material with stir casting fabrication method has been discussed. A strategic conceptual design approach, energy saving model and prototype development have been presented with the milestone towards automotive brake rotor application. The systematic and step-by-step approach of full design has been shown for better understanding of the design concept of automotive brake rotor. The author also highlighted finite element (FE) simulation and actual braking analyses for thermal performance stability whereas actual braking test result using a passenger car (Proton Wira 1.3) brake system rig set up to capture thermal distribution on the brake rotor surface.